Особенности онтогенеза Drimiopsis maculata Lindl et Paxt. в условиях защищенного грунта Донецкого ботанического сада НАН Украины - Прилуцкая, С.А. (Промышленная ботаника, 2004)
Ontogenetic stages of Drimopsis maculata Lindl. et Paxt. (Hyacinthaceae Batsh.) have been described under development from seeds of own reproduction. Their terms, duration and morphologic peculiarities have been determined. Biomorphologic characteristics of seeds, sowing qualitative features are investigated. Peculiarities of seed germination and real seed productivity under conditions of introduction to the conservatories of the Donetsk Botanical Gardens Nat. Acad. Sci. of Ukraine have been studied.